FRI0486 Cardiac cine mri in erdheim-chester disease: data from a large italian cohort. (23rd January 2014) - Campochiaro, C.; Cavalli, G.; Berti, A.; Guglielmi, B.; Carruthers, D.; Sabbadini, M. G.; Dagna, L.
Abstract : Background: Erdheim-Chester disease (ECD) is a rare, inflammatory disease of unknown etiology, characterized by xanthogranulomatous infiltration of tissues by foamy, CD 68+, CD1a-, S-100- macrophages [1 ]. ECD almost invariably involves long bones but may also feature extra-skeletal involvements. Cardiovascular and neurological involvements in particular are associated with the worst prognosis [2 ]. Objectives: To investigate the role of cardiac cine Magnetic Resonance Imaging (MRI) in detecting heart involvement and functional impairment in ECD. Methods: Six patients with histologically-proven ECD and cardiac involvement previously demonstrated by echocardiography and/or contrast enhanced CT scanning, underwent morphological and ECG-gated MRI with mitral/tricuspid transvalvular flow evaluation and study of myocardium viability after infusion of paramagnetic contrast agent. Results: In all cases, cardiac cine MRI detected the presence of infiltrative pathological tissue which typically showed a non homogeneous signal in STIR sequences, in accordance with the presence of adipose tissue, and late focal enhancement, indicating the presence of a fibro-granulomatous component. In our cohort of patients the infiltrated heart structures were: right atrium in all cases (100%), left atrium in two patients (33%), interatrial septum in one case (16%), right coronary artery with preserved flow, in four patients (66%), right atrio-ventricular sulcus in four patients (66%), left atrio-ventricular sulcus in one case (16%). In five patients (83%) the MRI disclosed the presence of pericardial effusion (three patients had circumferential pericardial effusion, two patients had only posterior pericardial effusion) with thickened pericardium, medium size 2.6 mm (range 1.5 – 4 mm). The right ventricle (RV) end-diastolic volume (EDV) and the left ventricle (LF) EDV were reduced in five patients (83%), medium volume 80 mL (range 60 – 90 mL) and 98.8 mL (range 92 – 107 mL) respectively. The RV and LF ejection fractions were always normal. The RV and LV diastolic functions were abnormal in all cases: in four patients the E wave was not recognizable, in two cases the E/A wave ratio was inverted. Conclusions: Cardiac cine MRI is a reproducible, non-invasive, operator-independent [3 ] technique that is extremely useful to identify the pathological infiltrate of ECD, to precisely define the anatomical location and extension of the disease, and to quantify the cardiac functional impairment. Cardiac cine MRI is thus a fundamental tool to assess the severity of the disease and to objectively follow-up its progression. References: Haroche, J., L. Arnaud, and Z. Amoura, Erdheim-Chester disease. Curr Opin Rheumatol. 24 (1): p. 53-9. Haroche, J., et al., Cardiovascular involvement, an overlooked feature of Erdheim-Chester disease: report of 6 new cases and a literature review. Medicine (Baltimore), 2004. 83 (6): p. 371-92. Gupta, A., et al., Cardiac MRI in restrictive cardiomyopathy . Clin Radiol. 67 (2): p. 95-105 Disclosure of Interest: None Declared